Organizational and pedagogical principles of methodical work in preschool educational establishments of Ukraine (the second half of the 20th century) - Chagovets, Alla; Syrova, Yu. (My University, 2017)
The research highlights the results of the historiographical analysis of organizational and pedagogical principles of methodical work in preschool educational establishments of Ukraine in the period of the second half of the 20th century. Three stages of organizational and pedagogical principles of methodical work in preschool educational establishments have been separated: the first stage is the 1950-s; the second stage is 1960-1983; the third stage is the middle of 1984-1999. It was found out that the theoretical investigations of scientists on the first stage concerned the questions of improvement of methodical work of preschool educational establishments’ heads. The second stage has been characterized as the stage of generalization and wide application of theoretical basis of methodical work in practical activity of preschool educational establishments. It was proved that the theoretical rethinking and creative reorganization of the bases of methodical work had been occurred on the third stage. It has been figured out that it is worth to rethink and use creatively valuable pedagogical experience of the methodical work in kindergartens in the second half of the 20th century with the aim of improvement of methodical work organization in modern preschool educational establishments. It has been determined that we can single out among valuable pedagogic aspects of methodical work organization such as the organization of methodical depositories, systematic conducting of practical seminars and videoconferences, the organization of patronage of children’s institutions, the organization of methodical associations on a voluntary basis, opening schools at kindergartens to study advanced pedagogical experiences and others.
Chagovets А. Organizational and pedagogical principles of methodical work in preschool educational establishments of Ukraine (the second half of the 20 th century) / A. Chagovets, Yu. Syrova // Development and modernization of social sciences: experience of Poland and prospects of Ukraine : collective monograph. – Lublin : Izdevnieciba «Baltija Publishing», 2017. – Vol. 3. – P. 243–259.
Keywords: організаційно-педагогічні засади, методична робота, дошкільні навчальні заклади, розвиток, етап, теорія, практика; organizational and pedagogical principles, methodic work, preschool educational institutions, development, stage, theory, practice